KOMUNIKASI PADA ANAK PUTUS SEKOLAH (Studi Kasus Di Keluarga Nelayan Wonorejo Banyuputih) - NUR AINIYAH (LP2M Universitas Ibrahimy, 2015)
This study is focusing on communication pattern of educational communication of fishermen children. The purpose of this study was to describe the education of fishermen children do not get stuck on dropout. So the focus (1) How does the social reality of fishing families in Wonorejo? (2) What are the perceptions of parents in regard to education for children? (3) How are the communication patterns of education in the family of fishermen to raise awareness of children in education? this research based on the qualitative analysis by reducing, observating, interviews and documents. The results of study that fishing are poor, that makes difficully to pursue their education to higher levels, it triggers the child has a